"Talking" as a Romantic Interaction: Is There Consensus?. Issue 4 (2nd October 2021) - Powell, Darcey N.; Freedman, Gili; Jensen, Katherine; Preston, Victoria
Abstract: Emerging adults (EAs) use many phrases to refer to their romantic interactions. In two studies ( N1 = 110; N2 = 222), EAs' knowledge and perceptions of "talking" were examined. In Study 1, a majority of college students had heard of "talking, " and perceived "talking" as distinct from "friends with benefits" (FWB) and dating. In Study 2, about half of a broader EA sample had heard of "talking" and perceived "talking" as being significantly less emotionally and physically intimate, and less committed than dating; they did, however, perceived "talking" to be similar in some ways to being FWB. Additionally, EAs varied in their agreement regarding the what, why, and how of "talking." Incorporating these results into youth relationship education programs may be beneficial to promoting healthy relationship development and reducing relational uncertainty.